3D Fish Culture - Krishnan, Yoghender (Universiti Teknologi PETRONAS, 2016)
Fish farming is been developed widely at all around the world, this is to overcome the problem of raise in demand for protein products and high volume of protein source can be found in fish. The most famous method that is been used for fish farming is the traditional method that occupies large area of space, required a lot of manpower for maintenance job, and need high electricity to run the system. In this project the fish farming requires less manpower for monitoring and maintenance purpose, renewable energy is used to run the system, and basic needs of the fish is provided in order to produce a good quality fish, like food dispenser and water current so that the fish will keep on moving. For the water filtration part, a Bio filter is included to remove all the waste products.